2017
DOI: 10.3389/fimmu.2017.01760
|View full text |Cite
|
Sign up to set email alerts
|

AS03- and MF59-Adjuvanted Influenza Vaccines in Children

Abstract: Influenza is a major cause of respiratory disease leading to hospitalization in young children. However, seasonal trivalent influenza vaccines (TIVs) have been shown to be ineffective and poorly immunogenic in this population. The development of live-attenuated influenza vaccines and adjuvanted vaccines are important advances in the prevention of influenza in young children. The oil-in-water emulsions MF59 and adjuvant systems 03 (AS03) have been used as adjuvants in both seasonal adjuvanted trivalent influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 180 publications
0
74
0
2
Order By: Relevance
“…Further, this situation may be exacerbated by the notice that the licensed vaccines based on a VADS are functioning to elicit immunity against pathogens without loading Ags to carriers via encapsulation or adsorption. And they are manufactured mostly through admixing Ags with liposomes, or other NPs, even just before immunization, as exemplified by Shingrix® vaccines which are supplied with separated packages of Ag and VADS [126].…”
Section: Ag Release and Liposome Integrity In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Further, this situation may be exacerbated by the notice that the licensed vaccines based on a VADS are functioning to elicit immunity against pathogens without loading Ags to carriers via encapsulation or adsorption. And they are manufactured mostly through admixing Ags with liposomes, or other NPs, even just before immunization, as exemplified by Shingrix® vaccines which are supplied with separated packages of Ag and VADS [126].…”
Section: Ag Release and Liposome Integrity In Vivomentioning
confidence: 99%
“…VADSs based on other micro−/nanoparticles, such as metal (gold, silver, iron) NPs, inorganic (silica) NPs and polymeric NPs, though have also showed a few advantages over conventional formulations in fulfilling functions of delivery and adjuvant, are mostly in early development [134]. An emulsion-based VADS, MF59, approved to Novartis for delivery of influenza vaccines, is a defined formulation consisting of o/w emulsion of squalene/Span85 /Tween80/water [162], which was later reformulated by GSK as an emulsion of squalene/α-tocopherol/ Tween 80/water, known as AS03 [126]. However, unlike liposomes, emulsions are in fact a very fragile carrier having a limited capacity to allow surface modification with functional materials, such as targeting molecules, to form a diverse VADS for delivering subunit vaccines.…”
Section: Perspectivesmentioning
confidence: 99%
“…Similarly, AS03 facilities a stronger antibody response by inducing a local cytokine and chemokine response at the injection site to enhance antigen uptake 43 . Studies in young children also showed that MF59-adjuvanted influenza vaccines produced a stronger and more homogeneous innate transcription response like that of adults, thus resulting in significantly higher HI titers than those elicited by non-adjuvanted vaccines 22 .…”
Section: Articlementioning
confidence: 95%
“…MF59-adjuvanted seasonal influenza vaccines were first licensed for the elderly in 1997 21 . AS03, another oil-in-water formulation of squalene, polysorbate 80, and α-tocopherol, allowed the mass production of pandemic influenza vaccines using reduced antigen dose during the 2009 global A(H1N1) pandemic 22 .…”
mentioning
confidence: 99%
“…Adjuvantierte Grippeimpfstoffe sind ein Weg, die bei manchen Per sonengruppen verminderte Immunogenität zu verbessern. Auch für junger Kinder konnten adjuvantierte IIVs entwickelt und er folgreich in klinischen Studien eingesetzt werden [17]. Insbeson dere bei Kindern, die noch keinen Kontakt mit Grippewild oder Impfviren hatten, ist dieser Ansatz vielversprechend.…”
Section: Adjuvantierte Grippeimpfstoffeunclassified